Microbial necromass accrual from newly added labile and native soil carbon in the rhizosphere vs. non-rhizosphere of broadleaved and coniferous trees - Juan Jia; Guoqing Zhai; Yufu Jia; Xiaojuan Liu; Keping Ma; Xiaojuan Feng (Geoderma)
Microbe-mediated carbon (C) transformation plays a crucial role in the accumulation of soil organic C (SOC). However, microbial conversion efficiency of newly-added labile C and native SOC to necromass remain under-investigated. Here we collected the rhizosphere and non-rhizosphere soils under broadleaved and coniferous trees of varying nutrient availability, and conducted an 80-day soil incubation with 13C-labelled glucose to evaluate ‘microbial C pump’ (MCP) capacity (new C-derived biomass and necromass), phospholipid fatty acids (PLFAs)-based C use efficiency (i.e., new C-derived PLFAs relative to respiration, referred as CUE′ to differentiate from microbial biomass C-based CUE) and amino sugar (reflecting necromass) accumulation efficiency (AAE; new C-derived amino sugars relative to respiration). We found that MCP capacity, microbial AAE and CUE′ had different variation patterns and influencing factors. The amount of added glucose played a decisive role in determining MCP capacity. The key predictors of AAE were the ratio of inorganic nitrogen (N) to added glucose (reflecting N limitation) and bacterial PLFAs, while ratios of fungi to bacteria and C to N were important for predicting CUE′. Furthermore, we found that glucose addition stimulated microbial transformation of native SOC into necromass in C- but not N-limited soils (with a high AAE) without invoking a priming effect, potentially enhancing microbe-mediated SOC sequestration. These findings suggest that the efficiency of microbial necromass accumulation is strongly influenced by N availability and decoupled from biomass synthesis, highlighting nutrient regulations on SOC sequestration via plant–microbe interactions. We argue that AAE is a more reliable indicator to assess the efficiency of MCP fueled by labile C.